Estimation of surface parameters from a 30 metre micro-meteorological tower over a deep moist convective region - PRADHAN, R.; DE, U. K.; SEN, P. K. (MAUSAM, 1996)
The estimation of u*, 0*, q*. and Obukov-length In the surface layer from micro-meteorological tower data still poses an important challange. In the present study a procedure for the parametric estimation has been developed which is consistent both with the similarity relation and the profile relation. The study has been done using both fast response and slow response tower data. Since similarity relations involve a particular level z. so inspite of starting from a layer, the parameters should be attributed to a relations involve a particular level only, It has been suggested that the convenient level is geometric mean height of the layer. The ratio of eddy diffusivities (KhKm.) has been estimated both for stable and unstable situation and this ratio is presented by a single expression which incidentally yields a new value of a constant involved.